Riesgo ecológico por dos productos farmacéuticos, diclofenaco e ibuprofeno, en Daphnia magna (pulga de agua), Paracheirodon innesi (pez tetra neón) y Lemna gibba (lenteja de agua) - Sanchez-Gonzales, Matvey (2025)
The ecological risk of the drugs diclofenac and ibuprofen was assessed in three indicator species: Daphnia magna (water flea), Paracheirodon innesi (tetra neon), and Lemna gibba (duckweed). Testing followed international guidelines and used the USEPA application to determine the LC(E)50. The Risk Ratio (RR) and Acute/Chronic Ratio (ACR) were calculated. L. gibba was the most sensitive species, followed by D. magna and P. innesi. From an ecotoxicological perspective, diclofenac poses a risk to freshwater macrophytes, while ibuprofen affects zooplankton, aquatic plants, and smaller fish. Guideline levels are suggested for both drugs to protect the aquatic ecosystem, establishing concentrations with no adverse effects on bioindicator taxa.